Massively parallel sequencing of complete mitochondrial genomes from hair shaft samples. (March 2015) - Parson, Walther; Huber, Gabriela; Moreno, Lilliana; Madel, Maria-Bernadette; Brandhagen, Michael D.; Nagl, Simone; Xavier, Catarina; Eduardoff, Mayra; Callaghan, Thomas C.; Irwin, Jodi A.
Highlights: We present a midi amplicon protocol involving two PCR multiplexes and amplicon sizes of 300–500 bp for massively parallel sequencing (MPS) of entire mitochondrial (mt)genomes from hair shaft samples. We evaluate alternative protocols using larger amplification products (2–3 kbp) as well as MPS from hair samples without prior amplification. Our study demonstrates that massively mtGenome sequencing is feasible from hair samples, which would significantly increase the discrimination power in forensic mtDNA testing. Abstract: Though shed hairs are one of the most commonly encountered evidence types, they are among the most limited in terms of DNA quantity and quality. As a result, DNA testing has historically focused on the recovery of just about 600 base pairs of the mitochondrial DNA control region. Here, we describe our success in recovering complete mitochondrial genome (mtGenome) data (∼16, 569 bp) from single shed hairs. By employing massively parallel sequencing (MPS), we demonstrate that particular hair samples yield DNA sufficient in quantity and quality to produce 2–3 kb mtGenome amplicons and that entire mtGenome data can be recovered from hair extracts even without PCR enrichment. Most importantly, we describe a small amplicon multiplex assay comprised of sixty-two primer sets that can be routinely applied to the compromised hair samples typically encountered in forensic casework. In all samples tested here, the MPS data recovered using any one of the three methods were consistent with the control Sanger sequence data developed from high quality known specimens. Given the recently demonstrated value of complete mtGenome data in terms of discrimination power among randomly sampled individuals, the possibility of recovering mtGenome data from the most compromised and limited evidentiary material is likely to vastly increase the utility of mtDNA testing for hair evidence.